1979
DOI: 10.1017/s0003356100023126
|View full text |Cite
|
Sign up to set email alerts
|

A note on the comparative growth performance of pigs sired by Piétrain × Hampshire, Hampshire × Large White and Large White boars

Abstract: The performance of progeny sired by Piétrain × Hampshire, Hampshire × Large White and Large White boars was compared over the live-weight range 28 to 65 kg. Feeding was twice daily to ‘appetite’ up to a maximum of 2·27 kg meal/day. Breed of boar did not influence rate or efficiency of live-weight gain, mid-line or internal fat depths nor muscle quality. Progeny of Pietrain × Hampshire and Hampshire × Large White sires, compared with those of Large White boars, had higher killing-out percentages (1·4 and 1·2 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Athough the data are not strictly comparable, other workers have also shown that breed variation in conformation has little effect on joint proportions and distribution of lean tissue (Smith et al 1973;Lishman & Smith 1979). Current interest in the condition known as pale, soft, exudative (PSE) muscle, coupled with lack of data on local breeds and the imported Duroc, were prime reasons for including muscle quality determinations in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Athough the data are not strictly comparable, other workers have also shown that breed variation in conformation has little effect on joint proportions and distribution of lean tissue (Smith et al 1973;Lishman & Smith 1979). Current interest in the condition known as pale, soft, exudative (PSE) muscle, coupled with lack of data on local breeds and the imported Duroc, were prime reasons for including muscle quality determinations in this study.…”
Section: Discussionmentioning
confidence: 97%